THE EFFECT OF GIBALA-STYLE EXERCISES ON DEVELOPING SOME BIOMOTOR ABILITIES AND BIOMECHANICAL VARIABLES OF THE SMASH SKILL IN YOUTH VOLLEYBALL - M.D. Ghaith Amir Aboud (Proximus Journal Publishing, 2024)
The smash is one of the offensive skills that affect the achievement of volleyball and through obtaining match points, which requires maximum effort from the player with accuracy of performance. The importance of biomechanics and kinetic analysis in knowing the details of movement of body parts, especially fast movements and their mechanical variables, and the relationship of these variables to other elements and variables that affect achievement or performance . Hence, the importance of this study came through preparing exercises using the Gibala method to develop some biomotor abilities and biomechanical variables of the smash skill in volleyball for youth, thus generalizing errors and enhancing positives in mastering the smash skill. The study aimed to prepare exercises using the Gibala method and identify the effect of exercises prepared using the Gibala method in developing some biomotor abilities and biomechanical variables of the smash skill in volleyball for youth
Keywords: Gibala; method in developing some biomotor; biomechanical